Perlindungan Hukum Terhadap Penumpang Ojek Online Yang Mengalami Kerugian Akibat Kecelakaan Tunggal - Nelly Elyta Neibaho; Dominikus Rato (Journal of Private and Economic Law, 2021)
The existence of information and communication technology often exceeds the speed of humans globally. One of the fields that modern society is interested in is transportation. Online transportation appears in the midst of a transportation system that is not well organized for some people, online transportation is a solution to a transportation system that is still bad, but on the other hand it is a problem for people who depend on services that do not rely on technology. Online motorcycle taxis are an alternative transportation that invites enthusiasm from the community. However, recently there has been an accident involving an online motorcycle taxi. The accident that occurred was a single accident where the accident occurred due to the negligence of a driver in carrying out his obligations. The research in writing this thesis uses normative juridical research, namely research that is focused on examining the rules or norms in the applicable positive law. The problem approach used is a statutory approach and a conceptual approach. The conclusions obtained from this study are: First, the form of loss for online motorcycle taxi passengers who suffer losses due to a single accident is material and immaterial. Second, the form of legal protection for online motorcycle taxi passengers who suffer losses due to a single accident is divided into two types, namely internal and external. Third, the settlement efforts taken by online motorcycle taxi passengers who suffer losses due to a single accident can be through litigation and litigation. Non-litigation namely negotiation, mediation, conciliation and arbitration. This study provides an overview to the Government and online motorcycle taxi entrepreneurs, especially PT. GOJEK to emphasize and clarify the rules related to licensing the use of motorcycles as public transportation or motorcycle taxis, both online and offline motorcycle taxis, as long as public transportation in Indonesia is not sufficient, so that with the rules that regulate clearly and firmly it will overcome the problem in the event of an accident single.